JUDICIAL PROBLEMATIC OF SURVEILLANCE JUDGE IN THE CONSTITUTIONAL SYSTEM OF THE REPUBLIC OF INDONESIA - Muhammad Fauzan (Faculty of Law, Universitas Jenderal Soedirman, 2016)
The presence of the Judicial Commission in the constitutional system of the Republic of Indonesia is mandated by the constitution of 1945, which in the execution of their duties and functions has provoked a variety of opinions, especially related to the supervision of judges who are considered to threaten the independence of the judicial power. Based on the results of discussion it is concluded that the juridical problematic which happens to the supervision of judges in the constitutional system of the Republic of Indonesia covering the First, unclear formulation of Article 24B of the Constitution 1945, especially related with the other authority of the Judicial Commission in order to preserve and enforce the honor, dignity, and the behavior of judges. The Second, it is related with the disharmony and inconsistency legislation regulations that controlling the supervision of judges, The Third, it is related to the institutional organization of the Judicial Commission and the Fourth, it is related to the vagueness of the definition of supervision. Keywords: problematic, Surveillance Judge, Indonesia